POTENSI BAKTERI INDIGENOUS RHIZOSFER TANAMAN BAWANG MERAH DALAM MENGHASILKAN SULFAT PADA TANAH VERTISOL DI BREBES, INDONESIA - JUWANDA, MUHAMMAD (Jenderal Soedirman University, 2022)
This study aims to obtain the best indigenous bacteria in increasing sulfate levels in vertisol soil through the oxidation process of sulfur to sulfate. The study was conducted in polybags with vertisol soil media in a screen house, Bulakelor Village, Keanggungan District, Brebes Regency. The experiment was arranged using a completely randomized design (CRD) with two factors. The first factor is the type of bacteria: Control (B0); Bacillus sp (B1); Burkholderia cepacia (B2); Klebsiella aerogenes (B3) and Klebsiella variicola (B4) and the second factor was incubation time: 3 (H3); 6 (H6); 9 (H9); and 12 (H12) days. Each treatment was repeated four times. Observation variables were soil sulfate levels (colorimetric method) and increased sulfate levels (calculation method). Observational data were analyzed using the F test and if there was a significant difference, it was continued with Duncan's test with 95% confidence level (Î± = 5%). The application of sulfur-oxidizing bacteria to vertisol soil can increase the availability of sulfate in the soil. The administration of Klebsiella variicola bacteria with an incubation period of 3 days increased sulfate levels by 69.11% better than the other treatments.